The Relationship Between Breakfast and the Learning Concentration of Students - Safitri, Maya; Prawitasari, Shinta; Ramba, Hardin La (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Breakfast is the first meal consumed in the morning before starting activities, usually before 10 a.m. Breakfast plays an important role because it provides 20-35% of the calories needed by the body to carry out daily activities. In addition to providing energy, breakfast can also improve concentration, memory, and information processing speed. Glucose obtained from breakfast supports nervous system activity, mood, and cognitive function. Cognitive function is very important in the process of learning, thinking, and decision making, and is greatly influenced by breakfast intake. Physiologically, the brain needs glucose as its main source of energy, and breakfast helps restore energy supplies after fasting overnight. This study used a quantitative approach with a correlational and cross-sectional design, involving 40 eighth-grade students with total sampling. The instruments used were questionnaires, digit symbol tests (DST), and observations. The results of the analysis using the Spearman rho test showed a positive relationship between breakfast and learning concentration, with a value of r = 0.521 and a value of p = 0.001. This study is expected to contribute to education and health policies, including education on the importance of breakfast to improve the quality of education in Indonesia.